Robotic Revolution in Thyroid Surgery: An Umbrella Review of Clinical Outcomes - Si‐Yue Yin; Ping‐Ting Zhou; Zi‐Hui Xie; Chuan‐Lu Shen; Fen‐Fen Li; Bing‐Yu Liang; Yi‐Pin Yang; Zi‐Yue Fu; Jian‐Peng Wang; Yan‐Xun Han; Shan‐Wen Chen; Cong‐Jun Zhang; et al. (OTO Open)
Abstract Objective This umbrella review aims to evaluate the clinical outcomes of robotic‐assisted thyroid surgery compared to traditional endoscopic and open surgical approaches. Data Sources We conducted a systematic search of PubMed, EMBASE, and Cochrane Database through August 2024. Review Methods We conducted a comprehensive analysis of systematic reviews and meta‐analyses that compare robotic‐assisted thyroid surgery with endoscopic or open methods. The primary outcomes assessed include surgical efficiency indicators, general postoperative complications, specific complications (nerve and endocrine), postoperative recovery and patient experience, and recurrence and long‐term prognosis. The methodological quality of the included reviews was assessed using the AMSTAR2 tool. Results Of the 1987 articles retrieved, 21 were eligible. Robotic surgery, though associated with longer operative times, offers distinct advantages in terms of precision. Although robotic surgery shows some variation in central lymph node dissection and an increase in postoperative drainage, its safety is comparable to both open and endoscopic techniques. Additionally, robotic surgery demonstrates superior cosmetic outcomes and shorter hospital stays from multiple approaches, though its high costs remain a significant factor. In terms of recurrence and survival rates, no significant differences were observed between robotic and open surgery. Conclusion Robotic surgery choices should balance benefits, costs, and patient needs. As technology and skills improve, efficiency and cost‐effectiveness may increase, expanding its clinical role.